2001
DOI: 10.2135/cropsci2001.413863x
|View full text |Cite
|
Sign up to set email alerts
|

Feed‐Quality Variation in the Barley Core Collection of the USDA National Small Grains Collection

Abstract: Feed is an important end use of barley (Hordeum vulgare L.). Recent research has identified high starch content, low acid‐detergent fiber (ADF), low ruminal dry‐matter digestibility (DMD), and large particle size after dry rolling as desirable barley feed‐quality characteristics for beef cattle. Knowledge about the variation available may help barley breeders develop strategies for feed‐quality improvement. Our objective was to estimate the variation in feed‐quality characteristics in barley around the world. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
62
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(75 citation statements)
references
References 22 publications
11
62
0
2
Order By: Relevance
“…ISDMD has been shown to provide reliable feeding performance results on a range of grains, including barley. Previous reports have shown the positive relationship between this assay and estimated feed performance 8,10 . A review by O'Brien 58 suggested that there is a lack of studies with sufficient experimental design to provide data on genotype and environment effects for in vivo assays.…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…ISDMD has been shown to provide reliable feeding performance results on a range of grains, including barley. Previous reports have shown the positive relationship between this assay and estimated feed performance 8,10 . A review by O'Brien 58 suggested that there is a lack of studies with sufficient experimental design to provide data on genotype and environment effects for in vivo assays.…”
Section: Introductionmentioning
confidence: 53%
“…A recent review highlights the important aspects of in vivo studies 44 . This process has been shown to provide data on performance of different grain species, and differences between cultivars 6,7,10,34,60,61 . In addition, the in-sacco method has been shown to provide more discrimination between or within species than an invitro assay.…”
Section: Introductionmentioning
confidence: 99%
“…Bowman et al 5 and Beecher et al 3 reported a relationship between hardness and ruminant feed quality from the Steptoe × Morex mapping population. The region on 5H associated with hardness was also confirmed from this study 3 .…”
Section: Figmentioning
confidence: 99%
“…However, recent studies have indicated that there is variation in barley that does impact feed performance 4,5 . Further, a considerable portion of malting varieties in any season, and in any country do not meet Tallon NRB01126 Tantangara NRB01133 Valier NRB01134 NRB01139 NRB01244 NRB01145 NRB01245 NRB01173 NRB01246 NRB01230 NRB01251 NRB01231 NRB01298 NRB01240 NRB01004 NRB01020 NRB01002 NRB01180 NRB01333 NRB01181 NRB01345 NRB01183 NRB01346 NRB01186 malt industry delivery standards and go into a feed classification.…”
Section: Feed Qualitymentioning
confidence: 99%
“…The addition of NSP-degrading enzymes to feeds was reported as a strategy to improve fibre utilisation, and thereby nutrient digestion in pig (Kerr & Shurson 2013). However, considerable variation exits CONTACT Prof. Aldo Prandini aldo.prandini@unicatt.it Istituto di Scienze degli Alimenti e della Nutrizione, Universita Cattolica del Sacro Cuore, Via Emilia Parmense 84, 29122 Piacenza, Italy in the fibre and starch contents as well as in starch type of barley grain leading to large variation in terms of digestible energy content (Bowman et al 2001;Jha et al 2010;Biel & Yacyno 2013).…”
Section: Introductionmentioning
confidence: 99%